2015
DOI: 10.1002/2015tc003904
|View full text |Cite
|
Sign up to set email alerts
|

The deformation record of olivine in mylonitic peridotites from the Finero Complex, Ivrea Zone: Separate deformation cycles during exhumation

Abstract: Mylonitic peridotites from the Finero complex are investigated to detect characteristic olivine microfabrics that can resolve separate deformation cycles at different metamorphic conditions. The heterogeneous olivine microstructures are characterized by deformed porphyroclasts surrounded by varying amounts of recrystallized grains. A well-developed but only locally preserved foam structure is present in recrystallized grain aggregates. This indicates an early stage of dynamic recrystallization and subsequent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 103 publications
(158 reference statements)
4
12
0
Order By: Relevance
“…Altenberger [15] suggested that the shear zones were related to the Variscan cycle. Matysiak and Trepmann [33] argued that the development of mylonites was connected to extensional tectonics in Jurassic times by analogy with what was reported for other shear zones in the Ivrea-Verbano Zone. The rare and unexpected occurrence of a single zircon grain within the fine-grained matrix of an ultramafic ultramylonitic sample (30F; Figure 10b,c) allowed us to discuss the age of activity of the shear zone.…”
Section: Timing Of Deformationmentioning
confidence: 58%
See 2 more Smart Citations
“…Altenberger [15] suggested that the shear zones were related to the Variscan cycle. Matysiak and Trepmann [33] argued that the development of mylonites was connected to extensional tectonics in Jurassic times by analogy with what was reported for other shear zones in the Ivrea-Verbano Zone. The rare and unexpected occurrence of a single zircon grain within the fine-grained matrix of an ultramafic ultramylonitic sample (30F; Figure 10b,c) allowed us to discuss the age of activity of the shear zone.…”
Section: Timing Of Deformationmentioning
confidence: 58%
“…Chromite-rich layers/pockets mainly occur in dunite, where they are broadly parallel to the high-temperature (HT) foliation [19]. In recent decades, the deformation processes within the mantle peridotites (Ph-Pd) and mafic/ultramafic rocks of the Finero Mafic Complex were the subject of multiple microstructural [1,2,[14][15][16][28][29][30][31][32][33] and geochemical/geochronological studies [17][18][19][20][21][22][23][24][25]27,33,34]. According to Tommasi et al [16] the mantle peridotite experienced a pervasive HT deformation in the presence of hydrous melts with crystallization of pargasite at T of about 980-1080 • C and P <2 GPa.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Stresses estimated based on recrystallized grain sizes (80–270 MPa) are higher than those inferred in the MDZs from the Bogota Transform. Preservation of small grain size (1.5–84 µm) may result from rapid exhumation after deformation and recrystallization (Matysiak & Trepmann, 2015), which is more likely in an extensional than in a transform setting. Postseismic relaxation characteristic times are small relative to those associated with the activity of the detachment faults and we do not observe evidence for a peak in stress followed by a relaxation period.…”
Section: Discussionmentioning
confidence: 99%
“…During exhumation and cooling of rocks the deformation conditions change and inherited ductile shear fabrics may not remain weak in the changing environment. Moreover, weak shear fabrics may be annealed during quasi‐static recrystallization processes, which would also help to recover the strength of the lithosphere (e.g., Matysiak & Trepmann, ; Trepmann et al, ). We therefore propose that the lithospheric‐scale reactivation of a rift‐inherited extensional detachment fault is unlikely and was probably restricted to the upper ~5–10 km.…”
Section: Discussionmentioning
confidence: 99%